Rare Association of Extended Total Colonic Aganglionosis and Intestinal Malrotation - Iulia Stratulat-Chiriac; Danielle Mc Laughlin; Brice Antao (EL-Med-Pub, 2020)
Total colonic aganglionosis occurring together with malrotation is a rare occurrence and may pose diagnostic and management dilemmas for the paediatric surgeon. We report a case of a neonate that presented with extended total colonic aganglionosis and malrotation, along with a spectrum of central nervous system and renal abnormalities. The clinical and radiological features and potential diagnostic and management pitfalls are discussed along with a literature review of this exceptionally infrequent association.